Calcium in pre-laying and laying rations on the performance and quality of laying hens’ eggshell - doi: 10.4025/actascianimsci.v35i2.16555 - Eliana Aparecida Rodrigues; Maria Cristina de Oliveira; Luciana Cardoso Cancherini; Karina Ferreira Duarte; Luis Fernando Santana; Otto Mack Junqueira (Acta Scientiarum. Animal Sciences, 2012)
The experiment evaluated the effect of different calcium (Ca) levels in pre-laying and laying diets on the performance and egg quality of laying hens. Two hundred and fifty-six 16-week-old Brown Hisex pullets were housed in a conventional shed. The experiment had a completely randomized design with 4 x 2 factorial arrangement (four calcium levels - 0.8, 1.3, 1.8 and 2.3% in pre-laying phase; two calcium levels - 2.5 and 3.5% in laying phase), totaling eight treatments with four repetitions of eight birds per experimental unit. The experiment started with 16-week-old hens receiving pre-laying diets provided until they were 18 weeks old. At this period, the laying diets started. Four 28-day cycles were evaluated for the following variables: production and egg weight, feed intake, feed conversion, mass of eggs and eggshell quality. Results show that a good performance was obtained with 0.8% calcium level in the pre-laying phase, whereas in the laying phase the 3.5% calcium level provided greater weight egg and better eggshell quality.